Leaders in Juvenile Crime - Carlos Díaz; Eleonora Patacchini; Thierry Verdier; Yves Zenou (Institute of Labor Economics (IZA), 2021)
This paper presents a new theory of crime where leaders transmit a crime technology and act as a role model for other criminals. We show that, in equilibrium, an individual's crime effort and criminal decisions depend on the geodesic distance to the leader in his or her network of social contacts. By using data on friendship networks among U.S. high-school students, we structurally estimate the model and find evidence supporting its predictions. In particular, by using a definition of a criminal leader that is exogenous to the network formation of friendship links, we find that the longer is the distance to the leader, the lower is the criminal activity of the delinquents and the less likely they are to become criminals. We finally perform a counterfactual experiment that reveals that a policy that removes all criminal leaders from a school can, on average, reduce criminal activity by about 20% and the individual probability of becoming a criminal by 10%.
Keywords: C31; D85; K42; 330; crime leaders; social distance; criminal decisions; closeness centrality